A Multi-Objective Solution Approach for the Design of a Sustainable and Robust System of Wastewater Treatment Plants: The Case of Chile - Vasquez-Perez, O; Espinoza-Perez, A; Jorquera-Bravo, N (Elsevier Ltd, 2023)
Water use has been growing at more than twice the rate of population increase in the last century. Combined with a more erratic and uncertain supply, this will aggravate the situation of currently water-stressed regions and generate water stress in areas with abundant water resources. It presents a major challenge for climate adaptation and raises the need for new sources of water resources. The research question, then, is whether there are sustainable supply chain configurations for wastewater reuse capable of operating with frequent changes in water demand and wastewater availability. Then, a multi-objective mixed-integer linear programming (MoMILP) model to provide an explicit description of the robustness concept is formulated. To illustrate the proposal s usefulness, the current situation in the center-north zone of Chile, where the availability and demand of water resources continue to fluctuate by natural and economic factors, is considered. The results provide five robust and sustainable supply chain configurations for wastewater reuse alternatives. They guarantee to meet the minimum demand for the resource with the amount available in any scenario. These results could be the basis for governmental policies related to tenders for wastewater reuse plant development, considering water is a common pool resource. Finally, some theoretical and practical contributions, extensions, managerial implications, and future work are discussed to develop a robust and generalized approach for the generation of public plans and policies in the design of robust and sustainable wastewater treatment plant systems. © 2023 Elsevier Ltd